Inventarisasi Lalat Buah (Diptera: Tephritidae) pada Pertanaman Pepaya di Kabupaten Ogan Ilir, Sumatera Selatan - Rasyid, Muhammad; Anggraini, Devi; Monalisah, Monalisah; Noviani, Noviani; Alfaiz, Salahuddin; Setiawati, Tiyas; Umayah, Abu; Gunawan, Bambang; Arsi, Arsi (Seminar Nasional Lahan Suboptimal, 2022)
Rasyid M, Anggraini D, Monalisah M, Noviani N, Alfaiz S, Setiawati T, Umayah A, Gunawan B, Arsi A. 2022. Inventory of fruit flies (Diptera: Tephritidae) on papaya plantation in Ogan Ilir Regency, South Sumatera. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang  27 Oktober 2022. pp. 768-776. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Management that can be done to reduce attacks from fruit flies is to use various traps such as the use of traps and aromas that are favored by fruit fly pests. The purpose of this study was to determine the species in papaya planting and determine the number of insect populations in Tanjung Pering Village, Permata Baru Village, and Timbangan Village, Ogan Ilir, South Sumatra. The method used in this study is the nisbi method, which is a method of looking at the population of fruit fly types by using heavy traps. From the research that has been carried out, as many as 15 steiner traps were successfully installed on papaya planting land in three villages. With the samples obtained, population counting and species identification in fruit flies can be done. There were 5 traps installed in Tanjung Pering Village, 5 traps in Permata Baru Village, and 5 traps in Timbangan Village. The steiner traps set in all three villages showed a diverse number of populations. As for the identification process, the results of the inventory of fruit flies on papaya planting fields were identified as species Bactrocera carambolae and B. kandiensis. The fruit flies that have been identified have differences from morphological characters, including thoracic color, abdominal pattern or pattern, wing shape, to the color of the limbs. The conclusion of the survey conducted in 3 villages was the number of samplings with the highest population was obtained in Timbangan Village and the lowest population was obtained in Tanjung Pering Village. That's why, further research must be held on these fruit flies, so that farmers get the right solution to overcome the problem of fruit fly pests that attack papaya plantations in Ogan Ilir regency, South Sumatra.